Engineering Strategies in Microorganisms for the Enhanced Production of Squalene: Advances, Challenges and Opportunities - Gohil, Nisarg; Bhattacharjee, Gargi; Khambhati, Khushal; Braddick, Darren; Singh, Vijai (Frontiers in Bioengineering and Biotechnology, 2019)
The triterpene squalene is a natural compound that has demonstrated an extraordinary diversity of uses in pharmaceutical, nutraceutical, and personal care industries. Emboldened by this range of uses, novel applications that can gain profit from the benefits of squalene as an additive or supplement are expanding, resulting in its increasing demand. Ever since its discovery, the primary source has been the deep-sea shark liver, although recent declines in their populations and justified animal conservation and protection regulations have encouraged researchers to identify a novel route for squalene biosynthesis. This renewed scientific interest has profited from immense developments in synthetic biology, which now allows fine-tuning of a wider range of plants, fungi, and microorganisms for improved squalene production. There are numerous naturally squalene producing species and strains; although they generally do not make commercially viable yields as primary shark liver sources can deliver. The recent advances made toward improving squalene output from natural and engineered species have inspired this review. Accordingly, it will cover in-depth knowledge offered by the studies of the natural sources, and various engineering-based strategies that have been used to drive the improvements in the pathways toward large-scale production. The wide uses of squalene are also discussed, including the notable developments in anti-cancer applications and in augmenting influenza vaccines for greater efficacy.